Green Architecture Strategies for Revitalizing Hybrid Traditional and Second-Hand Markets: The Case of Pasar Melati Medan - Lanny Kamila Iswiditya; Isnen Fitri (Journal of Environmental and Development Studies, 2026)
Pasar Melati, located in Medan City, functions as a hybrid traditional and second-hand market that plays a significant role in local economic and social activities. However, the market faces several critical issues, including poor spatial organization and circulation, inadequate waste management, limited natural ventilation, insufficient lighting, and a lack of green open spaces, all of which negatively affect user comfort and environmental quality. This study aims to propose a sustainable revitalization design for Pasar Melati by applying green architecture principles. A mixed-method approach was employed, combining field observations, spatial analysis, and semi-structured interviews with architects and market users to identify key problems and user needs. The findings indicate that the market requires improvements in spatial zoning, circulation systems, environmental comfort, and infrastructure management. The proposed design integrates green architecture strategies, including passive cooling through cross ventilation, natural lighting optimization, rainwater harvesting, waste segregation and composting, and improved spatial zoning to support both traditional and second-hand market activities. This study contributes to a green architecture-based design framework for hybrid markets, highlighting their role in sustainable urban development. Keywords: Circular Economy; Green Architecture; Hybrid Market; Market Revitalization; Passive Design